Differences between ceramic and porcelain laminate veneers - Alfaer, Ali Salem; Alfwais, Ryan Hussien; Al Haider, Yousef Masoud; Alghmdi, Raghad Abdullah; Qasim, Ammar Adel; Alkahtani, Dhuha Ayedh; Alsaeed, Sakinah Ali; Alqahtani, Nawal Ali; Alalyani, Amal Saleh; Alqhtani, Omar Ali; Yankesar, Rawan Ahmad (International Journal Of Community Medicine And Public Health, 2022)
In dental care, treating anterior dentition esthetically has always been difficult. Numerous restorative solutions, including resin composites, all-ceramic crowns, and ceramic veneers, become accessible with the advancement of dental materials. In such situations, practitioners and patients should pick the most appropriate option to enhance oral health and aesthetic outcomes. Any substance made of non-metallic inorganic matter and fired at an elevated temperature is referred to as ceramics (pyrochemical process). Ceramics called glass ceramics are those that commence in a glassy phase and later devitrify to a partly or wholly crystalline form. Dental ceramics that most closely optically resemble the characteristics of real teeth are primarily glassy materials, which are derived primarily from triaxial porcelain compositions of feldspar, quartz, and kaolin. Glass-ceramics possess much more toughness and strength than porcelain but are also less translucent. Tougher and more durable ceramics, primarily yttrium stabilized tetragonal zirconia polycrystals, have been developed recently (Y-TZP). Due to its limited translucency, Y-TZP presents a major drawback. A significant amount of current tooth structure must be removed in order to allow for a porcelain veneer that is wide enough to overlay an opaque zirconia base and replicate the optical characteristics of the surrounding natural teeth. Ceramic restoration effectiveness, in the end, relies on the material choice, production process, and restoration strategy.